Genetic Study of Resistance to Begomovirus on Chili Pepper by Hayman’s Diallel Analysis - Ganefianti, Dwi Wahyuni; Hidayat, Sri Hendrastuti; Syukur, Muhamad (International Journal on Advanced Science, Engineering and Information Technology, 2015)
Genetic study of resistance to Begomovirus is required in plant breeding program to obtain a resistance cultivar. Diallel analysis was used to evaluate the genetic parameters in early generation for Begomovirus resistance and agronomic characters. Fourty two hybrids and 7 selfed families generated from a full diallel cross of seven parental lines varying in Begomovirus resistance and yield potential were allotted in a randomized complete block design with three replications. Virus infection was made by inoculating ‘Segunung’ isolate from infected plant using Bemisia tabaci as the vector. Results showed that disease intensity, types of symptoms and fruit number were controlled by genes interaction. Fruit weight was controlled by additive gene actions, whereas incubation period were controlled by dominant gene actions. Disease intensity, types of symptoms and incubation period showed over-dominant gene actions towards lower intensity and longer incubation period respectively. The broad sense and narrow sense heritability for all characteristics are classified as moderate to high.